2016
DOI: 10.1039/c5nr08709k
|View full text |Cite
|
Sign up to set email alerts
|

Carbene-mediated self-assembly of diamondoids on metal surfaces

Abstract: N-heterocyclic carbenes (NHC)s are emerging as an alternative class of molecules to thiol-based self-assembled monolayers (SAMs), making carbene-based SAMs much more stable under harsh environmental conditions. In this work, we have functionalized tiny diamondoids using NHCs in order to prepare highly stable carbene-mediated diamondoid SAMs on metal substrates. Using quantum-mechanical simulations and two different configurations for the carbene-functionalized diamondoids attached on gold, silver, and platinum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 48 publications
8
25
0
Order By: Relevance
“…As shown in Figure b, the DFT calculated adsorption geometry of the debrominated intermediate on Cu(110) shows that it is stabilized by forming two C−Cu bonds with the substrate atoms. The surface‐stabilized intermediate is similar to the previously studied N‐heterocyclic carbene with unsaturated carbon atoms bonded to the surface, but different in the number of bonding (two C‐metal bonds with surface atoms as proposed here in Figure c, however in the reference the carbene C is found to be bonded to a single metal atom of the surface) …”
Section: Figuresupporting
confidence: 67%
See 1 more Smart Citation
“…As shown in Figure b, the DFT calculated adsorption geometry of the debrominated intermediate on Cu(110) shows that it is stabilized by forming two C−Cu bonds with the substrate atoms. The surface‐stabilized intermediate is similar to the previously studied N‐heterocyclic carbene with unsaturated carbon atoms bonded to the surface, but different in the number of bonding (two C‐metal bonds with surface atoms as proposed here in Figure c, however in the reference the carbene C is found to be bonded to a single metal atom of the surface) …”
Section: Figuresupporting
confidence: 67%
“…The surface-stabilized intermediate is similar to the previously studied N-heterocyclic carbene with unsaturated carbon atoms bonded to the surface, but different in the number of bonding (two C-metal bonds with surface atoms as proposed here in Figure 2c, however in the reference the carbene C is found to be bonded to a single metal atom of the surface). [36] After annealing the sample to~430 K, we observe the formation of ordered islands as shown in Figure 3a. From the close-up STM image (Figure 3b), we identify that the island structure consists of curved structures (as highlighted by blue contour) and bromine atoms.…”
Section: The Stereoselective Formation Of Trans-cumulene Through Dehamentioning
confidence: 99%
“…The BIM molecule selected for this study is schematically shown in Figure in the fully upright adsorption geometry on a Au(111) substrate. Assuming the length of the Au–C bond (∼0.21 nm) based on recent density functional theory (DFT) calculations, , the geometrical thickness of the BIM monolayer (taken from the Au atom) can be approximated as ∼0.85 nm. Based on DFT calculations, , at least three different bonding geometries between the carbene carbon atom and the Au(111) substrate should be considered for standing-up NHC SAMs, including (Figure ) (i) bonding to the surface atom in the on top position; (ii) bonding to the surface atom, which is pulled up from the surface; and (iii) bonding to the Au adatom.…”
Section: Resultsmentioning
confidence: 99%
“…However, as a chemical anchor, sulfur suffers from relatively low thermal and oxidative stability. , Recently, Crudden et al . proposed N-heterocyclic carbene (NHC) as a highly interesting alternative to form SAMs on gold via C–Au bonding. Generally, since their discovery by Arduengo et al ., carbene-based ligands in the form of NHCs have been widely used to form molecular complexes with transition metals and play crucial roles in many fields of catalysis and metal nanoparticle formation. , In contrast to typical carbenes, which are highly reactive and therefore exhibit notably limited stability, in NHCs, the carbene carbon atom has two adjacent heteroatoms of nitrogen that increase the stability of this compound to the level that enables long-term storage and further processing. Recently, it has been experimentally demonstrated ,,, and supported by theoretical calculations , that due to the higher stability of the Au–C bond than that of the Au–S bond, NHC-based SAMs on a gold substrate can exhibit ,, significantly higher thermal and chemical (oxidation, pH, electrochemical cycling) stability that than of standard SAMs based on thiols. However, as noted above, in addition to their high thermal/chemical stability, an equally important parameter that makes SAMs suitable for different applications, such as those related to molecular electronics or nanolithography, is their ability to form highly ordered and dense two-dimensional (2D) structures characterized by a low defect concentration.…”
mentioning
confidence: 99%
“…Accordingly, in the doped cases, one of the carbon atoms of the diamondoid cages are replaced by one of the dopants. For the functionalization molecules we have used (a) a thiol group (commonly used to attach diamondoids on a metal surface) and (b) the N-hetero-cyclic carbene (NHC) molecule, a member of the carbene family [11].…”
Section: Methodsmentioning
confidence: 99%